Pengaruh Pembelajaran Bahasa Arab Kontekstual Terhadap Efektivitas Hafalan Al-Qur’an Santri: Studi Kuasi-Eksperimen Di Pondok Pesantren Muhammadiyah Boarding School Yogyakarta - Fajar Shodik; Ahmadi; Eko Priyo Agus Nugroho (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aimed to examine the effect of contextual Arabic language learning on the effectiveness of Qur’anic memorization among students at Muhammadiyah Boarding School (MBS) Yogyakarta. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The sample consisted of 60 students selected through purposive sampling, comprising 30 students in the experimental group and 30 students in the control group. The experimental group received contextual Arabic language instruction based on the Contextual Teaching and Learning (CTL) approach, while the control group received conventional Arabic language instruction. Data were collected through a Qur’anic memorization effectiveness test covering fluency, accuracy of tajwid, accuracy of makhraj, memorization retention, and understanding of verse meanings. Data were analyzed using descriptive and inferential statistics, including normality tests, homogeneity tests, and the Independent Samples t-Test. The results revealed that the experimental group achieved a higher post-test mean score (87.63) than the control group (78.41). Furthermore, the Independent Samples t-Test showed a significance value of 0.000 (p < 0.05), indicating a statistically significant effect of contextual Arabic language learning on the effectiveness of Qur’anic memorization. The most notable improvements were found in memorization retention and comprehension of verse meanings. These findings suggest that contextual Arabic language learning is more effective than conventional instruction in enhancing the quality of Qur’anic memorization. This study provides important implications for the development of integrated Arabic language and Qur’anic memorization learning models in modern Islamic boarding schools.